Analysis of Financial Performance at Logitech International - Hasan, Dewi Khumairo'; Latifah, Umi (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2024)
Because of quickly change, technology industry also one of side that has experienced a correction, and many stocks that were previously considered high-flying and aggressively valued have suffered significant losses. Logitech, which this analysis focuses on. These companies trade at low valuations and offer promising growth potential and profitability. This research is library research analyzing the financial performance of the Logitech or LOGI’s company obtained from the official website, Logitech Annual Report, and related journal documents. This research found that Logitech's company generated 41.5 million in net income and had a total 4.54 in sales in the fiscal year 2023. With a current stock price of 89.78 in March 2024. The company's market capitalization is 10.32 billion, resulting in a P/E ratio of 29.10 slightly higher than the average industry of 28.28. Logitech is in a good financial health, as shown by its balance sheet. Its total assets have been increasing consistently. Logitech has consistently impressive returns on capital, exceeding 20%. Logitech has a healthy future financial outlook, profitability, and financial performance that make it attractive to value-oriented investors seeking opportunities in the technology sector.